2022
DOI: 10.3390/ijerph19053144
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Utilization of Institutional Delivery Services in Zambia: An Analytical Cross-Sectional Study

Abstract: Institutional delivery at birth is an important indicator of improvements in maternal health, which remains one of the targets of sustainable development goals intended to reduce the maternal mortality ratio. The purpose of the present study was to identify the determinants of utilization of institutional delivery in Zambia. A population-based cross-sectional study design was used to examine 9841 women aged 15–49 years from the 2018 Zambia Demographic and Health Survey. A multiple logistic regression was appli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Among the age categories of women delivering in health facilities, women belonging to 20-34 years age group had lower odds of institutional delivery as compared to the women of age less than 20 years. Further analyses of demographic and health survey conducted in different countries support the findings of this study [25][26][27][28].…”
Section: Institutional Deliverysupporting
confidence: 83%
See 1 more Smart Citation
“…Among the age categories of women delivering in health facilities, women belonging to 20-34 years age group had lower odds of institutional delivery as compared to the women of age less than 20 years. Further analyses of demographic and health survey conducted in different countries support the findings of this study [25][26][27][28].…”
Section: Institutional Deliverysupporting
confidence: 83%
“…Similar to other studies conducted in Nepal [24,29], this study also identified that women of higher wealth quintile were more likely than women with lower wealth quintile to give birth in a health facility. Other studies conducted in Ethiopia [27], India [25], and Zambia [28] found that the household wealth index was positively associated with institutional delivery.…”
Section: Institutional Deliverymentioning
confidence: 88%